2019
DOI: 10.3390/nu11010125
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Various Phytochemicals on Diverse Types of Thyroid Cancers

Abstract: Thyroid cancers developed from the tissues of the thyroid gland are classified into papillary (PTC), follicular (FTC), medullary (MTC), and anaplastic thyroid cancer (ATC). Although thyroid cancers have been generally known as mild forms of cancer, undifferentiated MTC and ATC have a more unfavorable prognosis than differentiated PTC and FTC because they are more aggressive and early metastatic. A variety of therapies such as surgery, radiotherapy, and chemotherapy have been currently used to treat thyroid can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 86 publications
0
30
0
1
Order By: Relevance
“…Isoflavones (genistein and daidzein) are abundant in soybeans derivative products and are known as RTK inhibitors, targeting the epidermal growth factor (EGF) and interfering with the cell proliferation, migration, and invasion mechanism [29]. Most of the studies on isoflavones are related to the antitumoral effects in hormonal dependent-cancer [19].…”
Section: Anticancer Effects Of Flavonoids In Lung Cancermentioning
confidence: 99%
“…Isoflavones (genistein and daidzein) are abundant in soybeans derivative products and are known as RTK inhibitors, targeting the epidermal growth factor (EGF) and interfering with the cell proliferation, migration, and invasion mechanism [29]. Most of the studies on isoflavones are related to the antitumoral effects in hormonal dependent-cancer [19].…”
Section: Anticancer Effects Of Flavonoids In Lung Cancermentioning
confidence: 99%
“…Papillary and follicular thyroid carcinoma are the most common types of DTCA [120]. Undifferentiated medullary and anaplastic thyroid cancer have, however, a less favorable prognosis than that for DTCA ( [121].…”
Section: Thyroid Status Imbalance Promotes Vfmentioning
confidence: 99%
“…Therefore, resveratrol holds the promise that it can protect the heart and fight the cancer at the same time. Since the anticancer properties of resveratrol have been discussed in a number of excellent reviews [27,104,105,106], we will focus here on the studies that demonstrated an additive and/or synergistic effect when resveratrol is combined with an anthracycline both in vitro (Table 3) and in vivo (Table 4).…”
Section: Anthracyclinesmentioning
confidence: 99%